Język, edukacja i media jako narzędzia ochrony dziedzictwa chrześcijan tradycji syriackiej w Iraku - Graczyk, Agnieszka (Humaniora. Czasopismo Internetowe, 2026)
The article examines the situation of Syriac tradition Christians in Iraq, a community that has shaped the cultural landscape of Mesopotamia for two thousand years and now faces the consequences of violence, forced displacement and demographic loss. It asks how a community marked by trauma can preserve continuity and rootedness. The text shows that the Syriac language, schooling, media and heritage initiatives play a central role, becoming both instruments of education and means of caring for memory and human dignity. The analysis demonstrates that, despite political and legal obstacles, the reconstruction of communal life results largely from human determination, including the efforts of families, teachers, clergy, local institutions and the diaspora. The article argues that the future of Syriac Christians depends not only on legal frameworks or state action but also on their ability to sustain the traditions that give meaning to their presence.